LEGALITAS JUAL BELI TANAH PERTANIAN BERDASARKAN HUKUM ADAT : STUDI PADA MASYARAKAT KECAMATAN ULUAN KABUPATEN TOBA SAMOSIR - RINTHUS MANURUNG (PREMISE LAW JURNAL, 2014)
ABSTRACT The implementation of an agricultural land trading business in Uluan Subdistrict, Toba Samosir District, which is still conducted based on Adat Law, yet with the enactment of Law No. 5/1960 on Basic Principle of Agraria, the unification of law in the field of land in the form of the uniform of right has been created that there is no more difference between the land with western rights and the land with customary rights.The implementation of trading business based on the Adat law practiced by the community in the research area is legal because it has met the legality of an agreement stated in Article 1320 of the Indonesian Civil Codes and becomes an evidence in court because it is written and a kind of the underhanded document, and in the process of registering the land, the National Land Board of Toba Samosir District accepts the agreement of the trading business as the basis to issue the certificate. Keywords : Legality, Trading Business, Agricultural Land, Adat Law